Modernisation of the lighting installation of a housing estate – case study - Ściężor, Tomasz (Instal, 2024)
Proper lighting of the place of residence at night, especially on winter evenings, is extremely important both in terms of ensuring safety and comfort of sleep at night. Unfortunately, housing estates built several dozen years ago are lit by archaic, usually largely neglected, HPS type luminaires, usually incorrectly installed. This lighting is most often insufficient, while generating various forms of light pollution. Currently, in Kraków, modern LED luminaires are systematically installed in housing estate lighting installations. The accusation is often raised in the media that the new lighting is not sufficient and is even worse than the previous one. In August 2023, the entire lighting installation of the Żywieckie Housing Estate in Kraków was modernised, which allowed these allegations to be verified. Comparison of the illuminance values   and luminance distribution in various parts of this estate before and after the above-mentioned modernisation allowed us to conclude that currently the lighting of its space is correct, ensuring the comfort of residents, while meeting the requirements of Polish lighting standards.
Keywords: light pollution; street and sidewalk lighting; illuminance; luminance; lamps; lighting fixtures; safety